The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1046/j.1462-2920.2000.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genes for alkane and naphthalene catabolism in Rhodococcus sp. strain 1BN

Abstract: Rhodococcus sp. 1BN was isolated from a contaminated site and showed various biodegradative capabilities. Besides naphthalene, strain 1BN degraded medium- (C6) and long-chain alkanes (C16-C28), benzene and toluene, alone or when the hydrocarbons were mixed in equal proportions. The nucleotide sequence of an alk polymerase chain reaction (PCR) fragment revealed a 59% nucleotide homology to the Pseudomonas oleovorans alkB gene. The nar fragments were highly homologous to genes coding for large and small subunits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…Recent advances in characterizing alkane metabolism in a number of organisms have allowed the production of a variety of primers to detect, for example, the alkB gene from P. putida GPo1 (573). As more strains are tested and more probes are produced, it is becoming clear that, while different alkane hydroxylases can be found in phylogenetically distant microorganisms (19), many probes will only provide information on the presence of a similar gene in closely related strains. Thus, the usefulness of such gene probes will grow as the diversity of genes responsible for hy-VOL.…”
Section: Culture-independent Approachesmentioning
confidence: 99%
“…Recent advances in characterizing alkane metabolism in a number of organisms have allowed the production of a variety of primers to detect, for example, the alkB gene from P. putida GPo1 (573). As more strains are tested and more probes are produced, it is becoming clear that, while different alkane hydroxylases can be found in phylogenetically distant microorganisms (19), many probes will only provide information on the presence of a similar gene in closely related strains. Thus, the usefulness of such gene probes will grow as the diversity of genes responsible for hy-VOL.…”
Section: Culture-independent Approachesmentioning
confidence: 99%
“…Comparison of the three alkane hydroxylase sequences showed that four histidine-containing motifs were well conserved, three of which were also present in the distantly related membranebound desaturases [51]. Based on two of the motifs, highly degenerate primers were developed that amplified internal gene fragments of alkB homologs from gram-negative as well as gram-positive strains [32,50,53,69] (Table 3). In the initial PCR study, most strains that were able to grow on alkanes yielded alkB gene fragments [50], and the same was found for a set of Rhodococcus strains isolated from soil in Bremen, Germany [86,87].…”
Section: Diversity Of Membrane-bound Alkane Hydroxylase Systemsmentioning
confidence: 99%
“…Sequencing of these PCR products after cloning confirmed their homology to alkB. Derived protein sequences showed highest homologies to AlkB from other bacterial gene (Smits et al, 1999;Khalameyzer et al, 1999;Andreoni et al, 2000;Kloos et al, 2006) …”
Section: Evaluation Of the Detection Methods With The Reference Isolatesmentioning
confidence: 79%